Strong, Bold, and Kind: Self-Control and Cooperation in Social Dilemmas - Martin G. Kocher; Peter Martinsson; Kristian Ove R. Myrseth; Conny Wollbrant (Center for Economic Studies and ifo Institute (CESifo), 2013)
We develop a model that relates self-control and conflict identification to cooperation patterns in social dilemmas. As predicted, we find in a laboratory public goods experiment a robust association between stronger self-control and higher levels of cooperation. This means that there is evidence for an impulse to be selfish and that cooperative behavior requires self-control effort. Free-riders differ from other contributor types only in their tendency not to have identified a self-control conflict in the first place.
Keywords: C91; D03; H40; 330; self-control; cooperation; public good; risk; experiment